Rapid Metabolome and Bioactivity Profiling of Fungi Associated with the Leaf and Rhizosphere of the Baltic Seagrass Zostera marina - Lars-Erik Petersen (Marine Drugs, 2019)
Zostera marina (eelgrass) is a marine foundation species with key ecological roles in coastal habitats. Its bacterial microbiota has been well studied, but very little is known about its mycobiome. In this study, we have isolated and identified 13 fungal strains, dominated by Penicillium species (10 strains), from the leaf and the root rhizosphere of Baltic Z. marina. The organic extracts of the fungi that were cultured by an OSMAC (One-Strain−Many-Compounds) regime using five liquid culture media under both static and shaking conditions were investigated for their chemical and bioactivity profiles. All extracts showed strong anti-quorum sensing activity, and the majority of the Penicillium extracts displayed antimicrobial or anti-biofilm activity against Gram-negative environmental marine and human pathogens. HPLC-DAD-MS-based rapid metabolome analyses of the extracts indicated the high influence of culture conditions on the secondary metabolite (SM) profiles. Among 69 compounds detected in all Penicillium sp. extracts, 46 were successfully dereplicated. Analysis of SM relatedness in culture conditions by Hierarchical Cluster Analysis (HCA) revealed generally low similarity and showed a strong effect of medium selection on chemical profiles of Penicillium sp. This is the first study assessing both the metabolite and bioactivity profile of the fungi associated with Baltic eelgrass Z. marina.